Salmonella Typhimurium TTSS-2 deficient mig-14 mutant shows attenuation in immunocompromised mice and offers protection against wild-type Salmonella Typhimurium infection - Pati, Niladri Bhusan (BioMed Central, 2013)
BACKGROUND: Development of Salmonella enterica serovar Typhimurium (S. Typhimurium) live attenuated vaccine carrier strain to prevent enteric infections has been a subject of intensive study. Several mutants of S. Typhimurium have been proposed as an effective live attenuated vaccine strain. Unfortunately, many such mutant strains failed to successfully complete the clinical trials as they were suboptimal in delivering effective safety and immunogenicity. However, it remained unclear, whether the existing live attenuated S. Typhimurium strains can further be attenuated with improved safety and immune efficacy or not. RESULTS: We deleted a specific non-SPI (Salmonella Pathogenicity Island) encoded virulence factor mig-14 (an antimicrobial peptide resistant protein) in ssaV deficient S. Typhimurium strain. The ssaV is an important SPI-II gene involved in Salmonella replication in macrophages and its mutant strain is considered as a potential live attenuated strain. However, fatal systemic infection was previously reported in immunocompromised mice like Nos2(−/−) and Il-10(−/−) when infected with ssaV deficient S. Typhimurium. Here we reported that attenuation of S. Typhimurium ssaV mutant in immunocompromised mice can further be improved by introducing additional deletion of gene mig-14. The ssaV, mig-14 double mutant was as efficient as ssaV mutant, with respect to host colonization and eliciting Salmonella-specific mucosal sIgA and serum IgG response in wild-type C57BL/6 mice. Interestingly, this double mutant did not show any systemic infection in immunocompromised mice. CONCLUSIONS: This study suggests that ssaV, mig-14 double mutant strain can be effectively used as a potential vaccine candidate even in immunocompromised mice. Such attenuated vaccine strain could possibly used for expression of heterologous antigens and thus for development of a polyvalent vaccine strain.